Disturbed Experience of Time in Depression—Evidence from Content Analysis - Vogel, David H. V.; Krämer, Katharina; Schoofs, Theresa; Kupke, Christian; Vogeley, Kai (Frontiers in Human Neuroscience, 2018)
Disturbances in the experience of time have been a commonly reported feature of depressive disorders since the beginning of modern psychiatry and psychological research. However, qualitative research approaches to investigate the phenomenon are rarely used. We employed content analysis to investigate disturbances of time experience in Major Depressive Disorder. Our analysis from 25 participants showed that individuals with Major Depressive Disorder subjectively seem to have lost the ability to influence or change the present, resulting in an impersonal and blocked future. The present is rendered meaningless, the past unchangeably negative, and the passage of time turned into a dragging, inexorable, and viscous continuance. The overall, - possibly intersubjective - concept of time experience, remains largely intact, causing or adding to depressive mood and suffering. We elaborate on how these findings reflect previous theories on the experience of time in depression. This study might encourage future inquiries into both the phenomenal and neuroscientific foundation of time experience under psychopathological conditions.